Solitary wave type solutions of nonlinear improved mKdV equation by modified techniques - Alhefthi, R. K.; Khan, M. Ishfaq; Sabi'u, J.; Marwat, D. Nawaz Khan; İnç, Mustafa (Soc Mexicana Fisica, 2024)
In this paper, the improved and modified version of the Sardar sub-equation method (IMSSEM) and the improved generalized Riccati equation mapping method (IGREMM) are manipulated effectively and generously to determine the exact solitary wave soliton solutions of the improved modified KdV (mKdV) equation. The purpose of this study is to provide novel exact solutions to the improved mKdV equation. Specifically, we utilized IMSSEM and IGREMM to study different solutions of the nonlinear improved mKdV equation, focusing on exponential, trigonometric, and trigonometric hyperbolic type solutions. Furthermore, the plotting of various solutions for direct viewing analysis is provided in two and three-dimensional graphs. The new strategies are straightforward, quick, and efficient and have many advantages, whereas, they provide the most accurate and unique solution to many other types of nonlinear partial differential equations (NPDEs), which usually arise in engineering and applied sciences. It should be noted that these methodologies are novel mathematical instruments that have shown to be the most effective mathematical tools for solving higher-order nonlinear partial differential equations mathematical physics. Symbolic computation was used to validate all of the solutions that were established. Thus, it is also hoped that techniques will ultimately reduce the cumbersome workload involved during the process of solutions to complicated NLPDEs.
Keywords: IMSSEM and IGREMM; improved mKdV equation; solitary wave solution; NLPDEs